The electrical properties of nanocluster-CdO/p-type silicon heterojunction structure at room temperature - Karatas, S.; Al-Ghamdi, A. A.; Al-Hazmi, Faten; Al-Hartomy, Omar A.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Natl Inst Optoelectronics, 2012)
The nanoduster CdO thin film was grown on p-type silicon substrate by sot-gel method. The structural properties of grown CdO film on Si substrate were investigated by atomic force microscopy (AFM). AFM images indicate that the CdO film is consisted of the clusters formed with coming together of the nano-particles. The heterostructure diode, formed from two semiconductor layers having different optical band gap, n-CdO/p-Si is prepared. The electrical properties such as barrier height, ideality factor, interface states density and series resistance of the n-CdO/p-Si heterojunction diode were determined from the current voltage (I-V) measurements. The values of barrier height and series resistance obtained from Cheung and Norde functions of the heterojunction diode were compared with each other. The interface state density (N-ss) as a function of energy distribution (E-ss-Ev) was extracted from the forward-bias I V measurements by taking into account the bias dependence of the effective barrier height (square(b)) and series resistance (R-s). The density of the interface state was found to vary from 7.52x10(12) eV(-1) cm(-2) to 5.07x10(12) eV(-1) cm(-2).
Keywords: Heterojunction semiconductors; Oxides; Nanostructures; I-V and C-V measurements